PELAKSANAAN STRATEGI PEMBELAJARAN AKTIF OLEH GURU PAI DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA DI SMPN 5 BATUSANGKAR - Isnani, Wilda (El -Hekam, 2019)
This study aims to find out how the implementation of active learning strategies in learning PAI in improving students' motivation in SMPN 5 Batusangkar. The method used in this research is qualitative research method by using descriptive approach, which become the source of data in this research is the teacher of religion which is the key informant, while the technique to test the validity of data of researcher use triangulation. The results of this study found data in the form of general findings and special findings. Specific findings in the form of implementation of active learning strategies by teachers in improving student motivation PAI in SMPN 5 Batusangkar. Specific findings of the implementation of this active learning strategy starts from the first: doing learning planning that consists of objectives, indicators, syllabus, design methods and strategies used. Second: the implementation consisting of the implementation of active learning strategies, media and evaluation are used, third: control consists of assessments made.